ANALISIS PERUBAHAN PENGGUNAAN LAHAN DI DAS BATANG TABIR KABUPATEN MERANGIN, PROVINSI JAMBI (Land Use Change Analysis in Batang Tabir Watershed Merangin Regency, Jambi Province) - Wirdatul Awaliyah Haryani; Dwi Putro Tejo Baskoro; Yayat Hidayat (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2023)
A continuous land use change in a watershed will affect the hydrological characteristics of the watershed. The Batang Tabir watershed has experienced a decrease in its carrying capacity shown by an increase in the frequency of flooding and the area of flood inundation. This study analyzes the land use changes in the Batang Tabir watershed, Merangin Regency, Jambi Province. The data used are DEM, topographic maps, river network maps, and Landsat imagery. Analysis of land use change used the Maximum Likelihood Classification (MLC) and the accuracy of image interpretation was carried out through the Kappa accuracy test. The land use prediction using the ANN model. The results showed that the rate of land use change increased in secondary forests, built-up areas, agriculture, and open areas; primary forests, paddy fields, and shrubs continued to decline. It is predicted in the year 2030, the trend will be the same; the built-up areas, agriculture, and secondary forests will increase, while primary forests, paddy fields, shrubs, and open areas will decrease.